Cross-Regional Comparison of Corruption - Linhartová Veronika; Pultarová Martina (WSEAS Press, 2015)
Regarding the fact that bribery and other forms of corruption are illegal in most countries, the participants of such practices strive thoroughly to hide them and uncovering corruption is often almost impossible. Even so, a large number of specific procedures exist nowadays. These procedures attempt to quantify corruption rates in each country. A common feature of these methods is however that they focus on corruption rates at the country level, but socio-economic development is not homogeneous from country to country. It can be assumed that corruption levels also differ in individual regions within the country. Sub-national areas which are more corrupt lower the rating of the corruption level in the entire country. Sub-national resolution in terms of corruption rates could bring a whole new dimension to the theory of cause and effect in the question of regional disparities. The main objective of this paper has been formulated in this context. A newly created index was used to verify corruption variability within the NUTS II regions in European countries. The high level of variability in corruption was confirmed between regions, particularly in Italy, but also in other countries. Because of this variability, it is in many cases very misleading to evaluate the country as a whole from the viewpoint of the impact of corruption.
Meziregionální komparace korupce
Keywords: corruption; regions; regional disparities; European Commission; regional policy; economic performance; korupce; regiony; regionální disparity; Evropská komise; regionální politika; ekonomická výkonnost